Akses Air Bersih di Indonesia - Sukartini, Ni Made; Saleh, Samsubar (Jurnal Ekonomi Kuantitatif Terapan; 2016: Vol. 9, No. 2, Agustus 2016 (pp. 89 - 176)DO - 10.24843/JEKT.2017.v09.i02.p01)
This study investigates household access on safe and clean water in Indonesia. The analysis is based on compilation data set of Statistic Indonesia and World Bank online publication namely INDO DAPOER ranging of 497 districts and municipalities for 2004-2011 periods.Our first analysis is the determinant of household access to clean and save water in district level. The second is combining access of clean and safe water with access on improve sanitation and ellectricty, to evaluate the impact on health indicator (morbidity rate) and district’s PDRB level. The third analysis is determining the impact of safe water,infrastructure, electricity and improved sanitation through morbidity rate and PDRB on the HDI. In general, this study find that better access on safe and clean water can improve community heath performance and district’s HDI. Better access on safe water should be followed by better access on sanitation, as these accesses are interlinked. Regarding intergovernmental transfer, an increase in DAU and DAK sectoral transfer are found improving health performance, increasing PDRB, HDI scor, and reducing poverty rate.
Keywords: access on safe water , morbidity rate , HDI